"Webside" healthcare from medical interns' perspective: Telemedicine implementation and need for training - Dalia Y. M. El Kheir; Razan A Alshamsi; Sukainah T Alalwi; Razan Z Alshammari (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Telemedicine involves the use of electronic communication and technology to remotely deliver clinical services to patients. With the increase in the adoption of telemedicine in healthcare delivery, "webside healthcare" is becoming the virtual analog of bedside care. The Ministry of Health in Saudi Arabia has recently established the use of telemedicine, including social media (SM) and medical applications (Apps) to enhance the quality and accessibility of healthcare services to patients and healthcare providers. In the present study, we evaluated medical interns' perception of the use of telemedicine, SM, and medical Apps in patient care, their awareness of related guidelines to find out if targeted training is needed. MATERIALS AND METHODS: A qualitative study recruited and interviewed, through semi-structured key informant (KI) interviews and focus group discussions (FGD), a total of 24 male and female medical interns. The Interns were purposefully sampled from all Saudi Arabia's 5 main geographical regions until data saturation was observed. The transcripts of five KI interviews and 6 FGDs done were thematically analyzed and are presented as themes and subthemes. RESULTS: Medical interns discussed the advantages and disadvantages related to telemedicine, SM, and medical Apps in healthcare services. Overall, interviewees appreciated the role telemedicine, SM, and medical Apps play in the healthcare and for such particular specialties as family medicine and (tele-) psychiatry. However, the interns believed that training on the technical operational aspects of different telemedicine modalities with an emphasis on targeted education for related ethical and legal regulating guidelines was vital. CONCLUSION: Most interviewed medical interns had a positive perception of telemedicine and were willing to use it in their daily clinical practice. However, there were some challenges to its successful implementation such as prompt training on its proper use and clear ethical and legal guidance.